Left atrium remodeling predicts late recurrence of paroxysmal atrial fibrillation after second generation cryoballoon ablation - Andreea Motoc; Juan-Pablo Abugattas; Bram Roosens; Esther Scheirlynck; Benedicte Heyndrickx; Carlo de Asmundis; Gian-Battista Chierchia; Steven Droogmans; Bernard Cosyns (Cardiovascular Ultrasound, 2018)
Abstract Background Atrial fibrillation (AF) is the most common arrhythmia worldwide. Nowadays, AF ablation is a valuable treatment option. It has been shown that the left atrium (LA) diameter is a predictor of AF recurrence after cryoballoon ablation (CBA). Since it does not reflect the true LA size, we compared the role of different LA anatomical parameters using echocardiography for the prediction of AF recurrence after CBA. Methods We retrospectively included 209 patients (mean age 56.1 ± 13.6 years, male 62%) with paroxysmal AF undergoing CBA. A transthoracic echocardiography was performed in all patients. Results At a mean follow-up of 16.9 ± 6.3 months, AF recurred in 25.4% of the patients. LA anterior - posterior diameter (LAD), LA minimum volume (LAmin) and early AF recurrence were independent predictors of recurrence. Based on receiver operating characteristics, cut – off values for LAD and, LAmin were 41 mm, 23.69 mL, respectively. The negative predictive values for recurrence were 73% and 87.3% respectively. In patients with AF recurrence, a significant proportion (30.2%) showed LA longitudinal remodeling (LA superior – inferior diameter) even though classically measured LAD was normal. Conclusions Longitudinal LA remodeling plays an additional role for predicting AF recurrence after CBA, in patients without LAD dilation. Moreover, LAmin had a high negative predictive value and was an independent predictor of AF recurrence. Therefore, a more complete LA anatomical assessment allows a better prediction of AF recurrences after CBA.